“There's Genderqueers on the Starboard Bow”: The Pregnant Male in Star Trek. - KERRY, STEPHEN (Journal of Popular Culture (Wiley-Blackwell), 2009)
The article discusses how to link the television program "Star Trek," and queer theory. Transgender theory and gender queers are used to understand the pluralization of sexes and genders in "Star Trek." The transformations of the human body in the television program such as the impregnation of the character Charles "Trip" Tucker III are noted. The terms queer theory and queering are explored. The relationship of "Star Trek" to science fiction's utopian futures, male pregnancy, and androgyny are discussed.